2003
DOI: 10.1177/019263650308763505
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Mentoring to Job Placement in School Administration

Abstract: The purpose of this study was to investigate the effects of mentoring on job placement for preservice principals. Do preservice principals need mentoring?Do preservice principals use mentors? How is mentoring defined? What characteristics are used to identify potential mentors for preservice principals? Does mentoring effect job placement for preservice principals?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
(11 reference statements)
0
10
0
1
Order By: Relevance
“…Mullen (2012) also alluded to a critical-constructivist perspective when she referred to mentoring as a journey encompassing the mentor and the protégé in "learning that is open-ended, creative, and uncertain, as well as subject to unknowns" (p. 7). In relational mentoring, both the mentor and the protégé enter the relationship expecting to grow, learn, and be transformed by the relationship; consequently, relational mentoring has been identified as an outstanding approach for leadership development (Boerema, 2011;Crippen & Wallin, 2008;Hayes, 2019;Dimmock & Walker, 2004;Reyes, 2003;Villani, 2006).…”
Section: Definition Of Mentoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Mullen (2012) also alluded to a critical-constructivist perspective when she referred to mentoring as a journey encompassing the mentor and the protégé in "learning that is open-ended, creative, and uncertain, as well as subject to unknowns" (p. 7). In relational mentoring, both the mentor and the protégé enter the relationship expecting to grow, learn, and be transformed by the relationship; consequently, relational mentoring has been identified as an outstanding approach for leadership development (Boerema, 2011;Crippen & Wallin, 2008;Hayes, 2019;Dimmock & Walker, 2004;Reyes, 2003;Villani, 2006).…”
Section: Definition Of Mentoringmentioning
confidence: 99%
“…The majority of the researchers in the mentoring studies indicated that both time for mentoring sessions and length of time in the mentoring relationships are critical when it comes to effective mentoring relationships. Developmental mentoring embraces a relationship that often lasts longer than a year and emphasizes longer-range expertise (Reyes, 2003). New principals need time with their mentors to share experiences in similar contexts (Harris & Crocker, 2006;Hayes, 2019).…”
Section: Determinants Of Effective Mentoring Relationshipsmentioning
confidence: 99%
“…Samkvaemt Reyes (2003) getur handleiðsla verið með mismunandi haetti, svo sem einstaklingsbundin handleiðsla, jafningjahandleiðsla og hóphandleiðsla. Formleg handleiðsla er byggð á formlegum samningi á milli þess sem tekur að sér handleiðsluna og þess sem þiggur hana og fer fram á ákveðnum tíma.…”
Section: Stuðningur Og þJálfun Nýrra Stjórnendaunclassified
“…The success of mentoring in the support and development of novice principals is dependent on the quality of the mentoring relationship between the mentor and protégé (Scott, 2010). relationship that often lasts longer than a year and emphasizes longer-range expertise (Reyes, 2003). New principals need time with their mentors to share experiences in similar contexts (Harris & Crocker, 2006;Hayes, 2019).…”
Section: Determinants Of Effective Mentoring Relationshipsmentioning
confidence: 99%